Isotonic beverage consumer profile - Rodrigues, Kerolany Sheila; Sousa, Milena Ferreira de; Dutra, Mariana Borges de Lima; Kameyama, Oswaldo (Seven Editora, 2024)
Isotonic drinks are defined as a hydroelectric supplement for athletes with the purpose of auxiliary to hydration, therefore, to understand that more and what the needs of the public become necessary for innovations to be saved. A market research helps make decisions, pois provides data on the market, which helps the development of new products and marketing. Or present work you have as an objective to assess the consumption profile of isotonic beverages through a quantitative questionnaire. A research was carried out by the digital platform Google Formulas in which socioeconomic questions and consumer preferences are opened, such as taste, size, volume of packaging, addition of vitamins and influence of two adolescents and colors. Two participants 71.2% were consumers. The socioeconomic data state that the highest age group was 22-31 years and the highest participation of Minas Gerais. Regarding the practice of physical activities, 77.3% did some type of exercise and 42.7% did exercise for 1 hour. About 43.1% consume rarely and 39.2% at any time of the day. The main reason for consuming 65.9% hydration foi is not considered isotonic as a substitute for nenhuma drink. The main attributes raised in consideration of the acquisition of the foram or flavor, price and brand, and most of the information obtained through friends. Or liquid type and size of 500 mL would be or ideal. For how many years the participants are not influenced by the time of purchase. A research apontou a concern with the quantity of sodium and potassium. As the results, I observed that the same with practice and frequency of physical exercises, or consumption is not something common among the participants, despite the relationship with hydration. DOI:https://doi.org/10.56238/sevened2023.006-151